Analysis of Concrete Compressive Strength by Adding Plastic Waste as an Additional Material Mixed in Cement for Manufacturing Pavling Blocks - Anggraini, Irene; Purnama, Ikhwan Arief; Hafiyyan, Qalbi (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2025)
In daily life, plastic waste feels very close to us as humans. This type of waste is very difficult to decompose,which significantly disrupts both life on land and in the ocean. In this study, the use of heated plastic waste as an additive incement mixtures for making paving blocks is still rarely explored. The aim of this research is to examine the impact of usingplastic waste as an additive in cement mixtures. Additionally, the use of plastic waste as an additive in cement is based on theidea that plastic waste can be transformed into something useful to reduce the troubling amount of plastic waste. For this purpose,this study employs both the Literature Review Method and the Experimental Method to determine how the addition of plasticwaste in paving block mixtures affects the compressive strength of the paving blocks. In this study, plastic waste will be used asan additive to cement with the following compositions: 0% (ordinary concrete), 2.5%, 5%, and 7% of the cement weight. Theresults showed that paving blocks with a 2.5% plastic mixture achieved the highest compressive strength of 26.2 MPa at 21 days,while the highest water absorption was observed in the 5% plastic mixture, with a value of approximately 6.14%. Overall, thetotal strength exceeded the planned compressive strength of 20 MPa based on the SNI 03-0691-1996 standard, making it suitablefor road use with a B quality grade.